Dielectric Barrier Discharge Induced By Permanent Magnet In Attraction And Repulsion Conditions For Ozone Generator - Murdiya, Fri; Saputra , Ivan (International Journal of Electrical, Energy and Power System Engineering, 2020)
Ozone is used in various area including medicine, drinking water treatment and waste treatment. Ozone can be produced using dielectric barrier discharge which is supplied by high voltage. High voltage occurs in the dielectric barrier discharge such as air gap that it is as a result of the failure of air in maintaining its insulator properties. Power supply used in this study is a parallel resonant push-pull inverter using a fly back transformer. In order to produce good plasma in producing ozone, a magnetic filed is added to dielectric barrier discharge. In this study, a magnet was placed on each anode and cathode electrode with the condition of attraction (model I) and repulsion (model II). The addition of two magnets to each electrode was also carried out under the conditions of attraction (model III) and repulsion (model IV). It is shown that the plasma intensity in the model I and III was higher than model II and IV. The discharge current in the model I and III was higher than model II and IV. The highest ozone concentration was model III and the lowest ozone concentration was in model IV. Model I had a higher ozone concentration than model II.